FROM HISTORICAL SYMBOL TO COMMUNICATIVE EXPRESSION: THE SYMBOLIC TRANSLATION OF LIANGZHU TOTEMS - Zou, Zhibing; Sikka, Sakchai; Suwanthada, Prathabjai (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This article examines how Liangzhu totems are transformed from historical symbols into communicative expression through symbolic translation in contemporary cultural communication. Its central concern is not the renewed verification of the original meanings of these totems, but the ways in which they may be reconstituted as forms of cultural expression that are intelligible to the public once detached from their original contexts. Employing a qualitative research design, the study integrates literature review, image analysis, and interpretive induction to investigate Liangzhu jade artifacts and representative totemic motifs through the relationship among cultural meaning, symbolic structure, and conditions of communication. The findings indicate that the principal obstacle to the contemporary communication of Liangzhu totems lies not in their invisibility, but in the difficulty of making their deeper cultural meanings directly accessible to the public. On this basis, the article proposes a symbolic translation mechanism composed of meaning selection, structural reorganization, and contextual adaptation, arguing that the modern transformation of Liangzhu totems is not a matter of simply replicating original images, but of reorganizing the relationships among cultural core, structural logic, and communicative expression. Contextual feedback from public communicative settings represented by high-speed rail interior spaces further suggests that this mechanism can generate a relatively clear translational pathway between specific symbolic objects and real spatial environments.